2014
DOI: 10.1007/s11192-014-1489-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the accessibility of Internet references in leading general medical journals

Abstract: This study prospectively evaluates the accessibility of Internet references in leading general medical journals and explores the impact of their lost accessibility. We identified all original contributions published in five leading peer-reviewed traditional general medical journals and one leading on-line journal that were published at two time points (January 2005 and January 2008). We followed the sample prospectively for 5 years and determined the number of Internet references that remained accessible. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In fact, what has been mentioned in the article is consistent with the findings of many other studies [2][3][4]. A study conducted in 2013 showed that about half of the articles published in the British Medical Journal and The Lancet cited at least one URL and that these URLs had a half-life of 4.7 years [2].…”
supporting
confidence: 90%
“…In fact, what has been mentioned in the article is consistent with the findings of many other studies [2][3][4]. A study conducted in 2013 showed that about half of the articles published in the British Medical Journal and The Lancet cited at least one URL and that these URLs had a half-life of 4.7 years [2].…”
supporting
confidence: 90%
“…Wren et al (2006) state that the instability of links, and, with that, of the information they contain, will continue to occur progressively until there are improved policies for the preservation and conservation of these links. Rochon et al (2015) noted that, although the Internet presents many possibilities in terms of ease of access and being gratis, it also has drawbacks. Some of these drawbacks are not being able to access the right information due to the inability to locate the resource in cyberspace because it had been moved or had been deleted from the Web, or because it was on the Invisible Web.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have tried to find solutions to these problems. Examples are: Spinellis (2003), Hester et al (2004), Tajeddini et al (2011), and Moghaddam et al (2012) who opt for cooperation among all the participants in the process by creating an online archive with all the Internet material, to which all references are directed; Wren et al (2006), Moghaddam et al (2012), and Rochon et al (2015) who consider that the links to digital objects should be reviewed before the document is published so as to prevent the premature decay of the said URLs; and finally, Spinellis (2003) and Tajeddini et al (2011) who indicate that the creators of the information on websites should themselves keep copies of the material they have created so that, if needed, they could cooperate with those responsible for maintaining that website. For Wren (2008), this situation is unlikely because the authors of the information available on the Internet do not have enough time and expertise to perform this task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation